Antitumor action of an aminochromene derivative on human - derived lung adenocarcinoma xenograft model - E. A. Samishina; M. O. Dudina; E. V. Blinova; I. R. Suslova; O. N. Deryabina; D. S. Blinov; P. N. Zhdanov (Сеченовский вестник, 2019)
Aim. To study antitumor and anti - metastatic action of AKh-554, 2-Aminium-7-(Diethylamino)-4-(4-Metoxibenzo[d][1,3]dioxol-5-yl)-4H-chromene-3-carbonytril N-Acetylamino - ethanoate, on in vivo model of lung adenocarcinoma patient - derived xenograft model. Materials and methods. In 40 immunodeﬁcient nu/nu BALB/c female mice with heterotopic patient - derived lung adenocarcinoma xenograft model antitumor and anti - metastatic eﬀects of 2-aminochromene derivative, AKh-554 at dose 50 mg/kg intragastrically during 7 days, were explored. Laboratory animals were randomly designated into four groups - intact mice, control, referent drug and main group. We used Cyclophosphamide as referent drug. In the tumor tissue of the animals treated with the derivative through intragastric rout we quantitively detected TUBB3, ALK and c-MET/HFG levels.Results. AKh-554 more than 7.5 times decreases both the growth rate and size of xenograft tumor when compared with control group ( p =0.001), and possesses an anti - metastatic eﬀect. Experimental treatment up to 103±2 days increases the lifespan of tumor carriers ( p =0.001 when compared with the control; p =0.03 when compared with cyclophosphamide), and induces remission in 60% of all cases. The established eﬀect is due to activation of tumor cells apoptosis associated with decrease in tumor tissue ALK concentration (2.77±0.54 ng/ml; p =0.001 when compared with the control and cyclophosphamide). Experimental models demonstrate no signs of pharmacological resistance to AX-554, which is conﬁrmed by the absence of diﬀerences of c-MET/HFG tissue level in all the studied groups (0.16±0.07 ng/ml - control; 0.09±0.03 ng/ml - Cyclophosphamide; 0.10±0.04 ng/ml - AKh-554).Conclusions. AKh-554 more eﬀectively than Cyclophosphamide inhibits xenograft tumor growth and its metastatic activity. The compound increases more than 3.3 times when compared with the control the lifespan of experimental animals and induces remission of the malignant process in 60% of tumor carriers. The compound anticancer property is due to anti-ALK-mediated activation of tumor cells’ apoptosis and suppression of cell proliferation processes.